Multi-Sourcing Strategies for Tariff Mitigation in Datacenter Infrastructure Procurement - Bhatt, Amal (ExcelingTech, 2026)
This This study develops a comprehensive multi-sourcing framework enabling organizations to mitigate Calendar Year 2025 datacentre infrastructure tariff exposure through strategic supplier diversification across multiple countries of origin. Enterprise server, storage, and networking procurement faces unprecedented cost volatility driven by Section 301 supplemental tariffs imposing 25-27.6 percent duties on China-origin products while alternative origins including USMCA partners, Southeast Asian manufacturing hubs, and emerging Indian production facilities offer zero-tariff treatment. Drawing upon supply chain risk management theory and portfolio optimization methodology, this research proposes a Total Cost of Ownership framework that integrates origin-dependent tariff structures, logistics costs, quality considerations, and risk premiums to enable systematic supplier allocation decisions. This research makes three primary contributions to supply chain management literature. First, it extends portfolio optimization theory to origin-based supplier allocation decisions under trade policy uncertainty. Second, it develops an enhanced TCO framework incorporating origin-dependent tariff structures as primary decision variables. Third, it provides the first systematic examination of India as an emerging datacentre infrastructure manufacturing origin for international procurement. Implementation guidance encompasses a sixteen-week execution program, financial justification models demonstrating 12-18 percent TCO reduction potential, and governance mechanisms for dynamic portfolio management.